RANCANG BANGUN SISTEM INFORMASI MANAJEMEN ASET PADA SMK NEGERI 10 SURABAYA - Renaldi, Renaldi; Sagirani, Tri; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Abstract: SMK Negeri 10 Surabaya is a vocational high school at the city of Surabaya. The problems that occurred at at school today are recording of asset data, asset lending data, and asset recovery data which are still processed manually by using ledger and excel microsfot. The process is still manual has weaknesses are; the old record- keeping process, human error, damaged or loss of ledgers and reporting that still take a long time to manufacture. The solution to this problem is to create an asset registration information system based on the availability of existing assets and asset feasibility, the process of recording asset lending and asset recovery. So the results of the process can be made in the report for reference as information assets that must be replaced or not, asset lending and asset recovery. Final Results show that the system can assist the process to obtain information on assets that need to be replaced, asset borrowing and asset return, as well as in the recording and reporting of assets, asset lending and asset recovery on SMK Negeri 10 Surabaya can be done well .Keywords: asset management, borrowing, returns, assets